Utilization of Hospital Waste B3 from Complete Blood Count (CBC) Residue as Test Material of Germinating Tube for Vaginal Discharge (Candidiasis) Infection Detection: Subtopic Microbiology Practice - Slamet Riyanto; Wahyudha NL; Widiastuti (Future Science, 2025)
Sampling the patient's blood for a complete blood count (CBC) usually exceeds the need, so much of it is left, which is subsequently destructed as B3 hospital waste material. This phenomenon encourages researchers to use it to isolate its plasma as an ingredient for the detection of the fungus Candida albicans which causes vaginal discharge (Candidiasis) using the Germinating Tube method. The problem is that the Germinating Tube test procedure uses serum ingredients. Researchers want to prove that the plasma isolated from hospital B3 waste can be used as an alternative to serum in the Germinating Tube test. This research is an explorative experimental laboratory. Performed the Germinating Test using three plasma and serum samples, with three strains of Candida albicans and Candida tropicalis as the negative control, after performing the Germinating Tube test by comparing the serum material with the B3 waste-isolated plasma material, observing the germination of the fungus Candida albicans in the binocular microscopes at 40x magnification. Parametric data can be obtained by calculating the number of spores that have undergone germination per 10 fields of view; then, an independent sample test is carried out. Based on the results of the Independent Test of the sample test, it was found that there was no significant difference between using plasma and serum materials, with a significance value of 0.113 (> 0.05). Conclusion: Plasma isolation material for B3 waste from Whole Blood analysis can be helpful as a unique material for the Germinating Tube test for candidiasis detection in the Mycological subtopic practice.